A Rare Cause of Obstructive Sleep Apnea Syndrome: Retropharyngeal Lipoma. (21st August 2017) - Dilek, Okan; Kaya, Omer; Yilmaz, Cengiz; Soker, Gokhan; Gulek, Bozkurt; Akin, Mehmet Ali
Abstract : Lipoma is the most common benign mesenchymal neoplasm. About 16% of lipomas arise in the head and neck region, especially in the posterior neck. Large lipomas that originate from the retropharyngeal space may cause dyspnea, dysphagia, and snoring and occasionally may lead to obstructive sleep apnea syndrome (OSAS). Herein, we report a 45-year-old male patient with OSAS caused by a giant retropharyngeal lipoma with emphasis on CT findings.